SOCIAL MEDIA-DRIVEN PROCESS INNOVATION AND COMPETITIVE ADVANTAGE IN ART GALLERIES AND MUSEUMS: THE MEDIATING ROLE OF VISITOR CO-CREATION - Radiany, Ade Asria; Herdinata, Christian; Kodrat, David Sukardi (Fakultas Ekonomi dan Bisnis, UNTAN, 2025)
The purpose of this study is to analyze the influence of social media-driven process innovation on competitive advantage in art galleries and museums, with visitor co-creation as a mediating variable. Drawing on Dynamic Capability Theory (DCT), the study employs a quantitative design with PLS-SEM on 198 valid responses from Cultural and Creative Industry organizations registered with Indonesia